The Effect of Tax Planning and Tax Avoidance on Company Value with Net Profit Margin as an Intervening Variable in Retail Companies in Indonesia - Siagian, Aaron Jose; Safrudin; Karsam (Universitas Mohammad Husni Thamrin, 2026)
This study aims to analyze the effect of Tax Planning and Tax Avoidance on Firm Value with Net Profit Margin as an intervening variable in retail companies listed on the Indonesia Stock Exchange. Government spending and national development are supported by taxes, which constitute a substantial portion of domestic revenue. A country requires substantial financial support to implement its growth goals. Taxpayers must bear a significant obligation to contribute and enable government activities, while the government has the authority to collect taxes in accordance with the law. The study uses a quantitative approach with panel data of 19 retail companies for the period 2022–2024 processed using EViews 12, through a series of classical assumption tests, path analysis, Sobel mediation tests, and coefficient of determination (R-squared) tests. The results show that Tax Planning has a significant effect on Net Profit Margin, while Tax Avoidance has no significant effect on Net Profit Margin. On the other hand, Tax Planning, Tax Avoidance, and Net Profit Margin do not have a significant direct effect on Firm Value, although the three variables simultaneously explain approximately 90.11% of the variation in Firm Value. The results of the mediation test also show that Net Profit Margin does not mediate the influence of Tax Planning or Tax Avoidance on Company Value, so that the increase in the value of BEI retail companies is suspected to be more influenced by other factors outside the tax and profitability strategies tested in this study.